Peningkatan Produktivitas, Kualitas dan Pemasaran Kain Tenun Troso Berbasis Penerapan Iptek di Kecamatan Batealit, Kabupaten Jepara - Musdalifah, Musdalifah; Rachmadi, Moch Faizal; Khumaedi, Muhammad; Satyarini, Marhaeni Dwi (Universitas Mataram, 2025)
Indonesia is known as a country rich in cultural diversity, including in the arts, textile crafts, and the creative economy. One of the cultural heritages that the nation is proud of is woven fabric, which is spread across various regions with their own unique characteristics. Woven fabric not only reflects the cultural identity of a region but also has great economic potential for the local community. Each region in Indonesia has its own motifs, techniques, and philosophy in making woven fabric, including in Jepara Regency, which is known as the center of Troso woven fabric. However, in facing the era of modernization and global competition, Troso woven fabric entrepreneurs need to make various efforts to increase productivity and expand the market in the current digital era. The target partner is the Berkah Karya Joint Business Group (KUB) with an address in Bringin Village, Batealit District, Jepara Regency. The service method is through socialization, training, technology application, mentoring, evaluation, and program sustainability. The training provided on the diversity of fashion products based on Troso woven fabric that are innovative, creative, contemporary, and can be used by all levels of society, from children to the elderly. In addition, an emphasis on the zero-waste approach is also conveyed to the target partners. This aims to create sustainable business products. Assistance is provided on digital promotional content creation, packaging design, and market expansion efforts. This also includes assistance with the operationalization of machinery and Appropriate Technology (TTG) applied to target partners